Design of monitoring and control system of electricity power limiter using internet of things - Gunoto, Pamor; Yuliansyah, Toni; Nurdin, M.; Hisyamuddin, . (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Electrical energy efficiency usage is an important things in the modern era, especially to reduce costs and environmental impacts. This report discusses the design of monitoring and control system using Internet of Things (IoT) based power limiter, which is designed to monitor and manage electricity consumption in real-time. This system uses the PZM-004T sensor to measure electricity consumption by measuring current and voltage and then sending the data via the WiFi network to a cloud server. Users can access information related to electricity usage via web-based or mobile applications that provide data display in the form of a reports. This system is equipped with a notification feature in the application to provide warnings if excessive electricity consumption occurs, as well as the ability to control devices remotely to optimize electricity usage. By applying data analysis algorithms, this system is able to provide recommendations for better energy efficiency. The implementation of this system aims to increase user awareness about their electricity consumption patterns and provide practical solutions for more sustainable energy management